2004
DOI: 10.2307/3345522
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Overview of Sight-Singing Requirements of Large-Group Choral Festivals

Abstract: The purpose of this study was to examine sight-singing requirements at junior and senior high school large-group ratings-based choral festivals throughout the United States. Responses to the following questions were sought from each state: (1) Are there ratings-based large-group choral festivals? (2) Is sight-singing a requirement? (3) Are there specific levels or classes of difficulty ? (4) Is musical content specified for each level or class ? (5) Is there an overall rating that includes both the performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Each spring, students from more than 40 states of the United States are adjudicated in choral festivals (Norris, 2004), with judges most commonly using the traditional adjudication form. Although the music education profession purports the use of rating scales as beneficial for measuring performances, there is no research that explores the interrater reliability of an instrument that has a balanced combination of dimensions with descriptors-those beyond the vague &dquo;excellent, good, satisfactory, poor, and unsatisfactory.&dquo;…”
mentioning
confidence: 99%
“…Each spring, students from more than 40 states of the United States are adjudicated in choral festivals (Norris, 2004), with judges most commonly using the traditional adjudication form. Although the music education profession purports the use of rating scales as beneficial for measuring performances, there is no research that explores the interrater reliability of an instrument that has a balanced combination of dimensions with descriptors-those beyond the vague &dquo;excellent, good, satisfactory, poor, and unsatisfactory.&dquo;…”
mentioning
confidence: 99%
“…In addition, teachers in Demorest's (2004) study indicated that they assessed students individually. When combined with Norris' (2004) results, it could indicate that teachers in up to half of states in the United States taught sight-singing on a regular basis, but that other teachers in at least half of states might not have taught sightsinging regularly. Based on the research, it appears teachers in Florida and Texas who attended state festival most likely also taught sight-singing; because research studies have identified sight-singing instruction patterns within those state populations (Henry, 2004;Killian & Henry, 2005;Kuehne, 2007), perhaps music educators should take note of resources and techniques that teachers use in those states.…”
Section: Discussionmentioning
confidence: 79%
“…82 Fewer than half of all state organizations currently mandate sight-reading at largegroup festivals, and even fewer include the sight-reading score in the overall final rating. 83 Reasons might include lack of space at some contest sites, the desire to increase participation, or philosophical perspectives against adjudicating this skill. Regardless, sight-reading at festivals today-even if unrated-will encourage directors to focus on learning goals beyond the contest repertoire and provide a measurement of this important musical ability.…”
Section: Sight-readingmentioning
confidence: 99%